Minerals in Pregnancy and Their Impact on Child Growth and Development - Farias, Patricia Miranda; Marcelino, Gabriela; Santana, Lidiani Figueiredo; de Almeida, Eliane Borges; Guimarães, Rita de Cássia Avellaneda; Pott, Arnildo; Hiane, Priscila Aiko; Freitas, Karine de Cássia (Molecules (Basel, Switzerland), 2020)
During pregnancy, women undergo metabolic and physiological changes, and their needs are higher, to maintain growth and development of the fetus. If the nutritional status of the expectant mother is not satisfactory, some maternal and neonatal complications can occur. In the second and third trimester of pregnancy, there is a reserve of nutrients in the fetus that can be utilized after birth; thereby, children present an accelerated growth in the first years of life, which is a proven response to the available nutrition pattern. However, if such a pattern is insufficient, there will be deficits during development, including brain function. Therefore, despite many recent published works about gestational nutrition, uncertainties still remain on the mechanisms of absorption, distribution, and excretion of micronutrients. Further elucidation is needed to better understand the impacts caused either by deficiency or excess of some micronutrients. Thus, to illustrate the contributions of minerals during prenatal development and in children, iodine, selenium, iron, zinc, calcium, and magnesium were selected. Our study sought to review the consequences related to gestational deficiency of the referred minerals and their impact on growth and development in children born from mothers with such deficiencies